PENGARUH FAKTOR SOSIAL INDIVIDU TERHADAP PERILAKU BERBAGI PENGETAHUAN PADA GRUP YAHOO - , Eka Oktaviyanti Pramasinta, Dr. Sony Warsono, MAFIS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Knowledge is the asset of human beings, as well as a competitive advantage, a knowledge of existing and inherent in the human brain. Knowledge to benefits other individuals, because with knowledge a person can learn to develop the capacity and capability to achieve a specific goal. Knowledge would be more useful if it can be transfered to other people. That activity is called âknowledge sharingâ. Knowledge sharing is not only done in person or face to face but also through virtual communication using internet technology that allows individuals to connect to each other in a virtual community without any limitations of distance and time. Virtual knowledge sharing has become a phenomenon of technological developments virtually improve the knowledge especially of the virtual communities. This study raised the individual social factors in knowledge sharing through virtual communities. Object of this study is the Yahoo Group of UGM lecturers with 100 samples based on predetermined criteria. This study develops a theoretical model which consists of three hypotheses. The hypotheses were tested using multiple regression analysis techniques. The results note that the reputation of the most influential and reciprocity knowledge sharing behavior and cohesiveness has some impacts on knowledge sharing.